Implementasi Metode Pembiasaan dalam Pembentukan Karakter Mandiri Anak Usia Dini pada Masa Pandemi Covid-19 di Paud Bina Sejahtera I Gandaria Utara Jakarta - Fauziah, Erna; Afni, Zakiah Nur (El-Athfal : Jurnal Kajian Ilmu Pendidikan Anak, 2024)
The habit of forming independent character in early childhood during the pandemic is still hampered by limited space and time. Previously students studied online, since January 3 2022 students started school from 08.00 to 09.30. As a result of the transition from online to offline, students need social adaptation. The teaching and learning time is only 90 minutes from Monday to Friday, there is no rest time, the learning situation experienced by the students is not yet conducive. The aim of the research is to determine the application of the habituation method for forming independent character in early childhood in PAUD through interaction between teachers and students, using qualitative research methods, describing the concept of learning while playing and telling stories. Data collection techniques were obtained from interviews, observation and documentation, which were analyzed by data reduction, data presentation and drawing conclusions. The results of the research show that independent character in the form of changes in attitudes and behavior as a reflection of commendable morals in young children attending PAUD can be formed through the example of teachers and the habits they teach while students study at school.